Determining factors influence out-of-pocket health expenditure among the low-income group in Malaysia - Said, Rusmawati; Ismail, Norfatihah; Ismail, Normaz Wana (Human Resource Management Academic Research Society, 2020)
A substantial proportion of the population is still struggling to achieve socio-economic and good health, i.e., the low-income groups. The low-income group in Malaysia might bear a higher burden of out-of-pocket health expenditure (OOPHE) and health challenges, mainly related to noncommunicable diseases (NCD). The costs are sometimes high enough so that households cannot recuperate them from existing resources and lead them to financial problems. This study analyzed the factors associated with OOPHE among B40 group in Malaysia using nationwide data from the 2015 National Health and Morbidity Survey (NHMS). Ordinary Least Square (OLS) regression analysis is used to study the factors associated with OOPHE. This study suggests that the gender (female) of household, income, T20 income group, tertiary education, unpaid worker, retire, and NCD raises the likelihood of incurring OOPHE. The result for a private employee, self-employed, and insurance status is spending less on OOPHE. Therefore, the results show a clear need for government action to enhanced primary healthcare programs and a focus on achieving Universal Health Coverage. This situation can protect the household from OOPHE financial burden and NCD, exceptionally lowincome earners.